Assessment of Extranodal Lymphoma by 18F-FDG PET/CT A Report of two years in NINMAS - Mandal, Tapati; Mutsuddy, Pupree; Akhter, Papia; Rahman, Arifur; Mishal, Sazzad Al; Siddique, Abu Bakker; Begum, Shamim MF (Bangladesh Journal of Nuclear Medicine, 2024)
Extranodal lymphoma, characterized by lymphomatous infiltration beyond typical lymphatic structures, poses a diagnostic challenge due to its diverse clinical presentations. This cross-sectional study conducted at the PET/CT division of the National Institute of Nuclear Medicine and Allied Sciences, Dhaka, aimed to explore the prevalence and distribution of extranodal involvement in 517 lymphoma patients (252 Hodgkin’s lymphoma [HL] and 265 non-Hodgkin’s lymphoma [NHL]) referred for 18F-FDG PET/CT scans from January 2022 to December 2023. Results revealed extranodal involvement in 9.12% (n = 23) of HL cases and 34.71% (n = 92) of NHL cases. Skeletal system manifestations were most common, accounting for 28.7%, followed by pulmonary (23.4%), gastrointestinal tract (19.1%), and muscular (13.9%) involvement. Other sites collectively constituted 15.6% of extranodal lymphoma cases. These findings underscore the significance of 18F-FDG PET/CT scans in assessing extranodal lymphomas, providing valuable insights into their distribution patterns. Understanding the prevalence and locations of extranodal involvement is crucial for accurate diagnosis, staging, and effective treatment planning in lymphoma patients. Bangladesh J. Nuclear Med. 26(2): 177-183, 2023